Identity in contemporary international conflict: typology of the history of conflicts through the prism of an Other - D. V. Chernobrov (Vestnik MGIMO-Universiteta)
The problem of an Other and association with an identity in conflict are among the least explored areas of contemporary conflict studies which tends to regard conflict behaviour as rational. This article suggests several periods in the development and evolution of conflict depending on the role and function of the Other, thus adopting a historical-constructivist approach. From the spread of social application of self-other categories to conflict, to the technological and informational transition from traditional to ‘new’ and asymmetrical wars and counter-insurgency warfare, the Other changed form, function, and role in conflict. Supporting the argument with historical evidence, this article reconstructs the evolution of the Other and situates it in the context of social, political, and conflict-evolving realities.